EVALUASI PERCEPATAN PEMBANGUNAN PROYEK RUSUNAWA ASN PEMKAB MALANG MENGGUNAKAN METODE CRASHING DENGAN SISTEM SIHFT KERJA - Apriliana, Ninda Rizki; Gunasti, Amri; Kuryanto, Totok Dwi (Universitas Muhammadiyah Jember, 2020)
In construction projects there are three things that must be considered, namely time, cost and quality. However, reality shows that there is still often a delay time of implementation. One way to overcome delay in construction projects is to do with the crashing. This research was conducted on the project of the construction of the building Rusunawa ASN Malang Regency. The method of crashing used by wayof a work shift. The calculation of the needs of the work shift using the guidelines for the calculation of Unit Price Analysis of Workers (AHSP) in 2018. The results showed that the project can be accelerated for 24 working days, so the duration of the project which was originally 197 working days to 173 days of work. Direct costs the project has increased from Rp.12.763.192.497.58 in 197 days to Rp. 12.937.000.000.00 in 173 days (up 1,3554%).